Aortitis caused by Abiotrophia defectiva: Description of two cases - David Nygren; Martin Älverbrandt; Torgny Sunnerhagen; Erika Fagman; Ellen Ostenfeld; Magnus Rasmussen (MDPI AG, 2018)
Abiotrophia defectiva is a well-known endocarditis pathogen, however it has never been described as a cause of primary aortitis. Here we describe the first published case of thoracic aortitis and an unusual case of aortic graft infection due to A. defectiva, which were both managed conservatively.